Memahami Fungsi Keluarga dalam Perlindungan Anak - Fatimaningsih, Endry (JURNAL SOSIOLOGI, 2015)
The family got a major task in child protection. Because of the family the child is born, grow, and thrive. Through a variety of functions, the family is expected to be able to fulfill these responsibilities. This literature study intends to identify the various family functions related to child protection efforts. The results show that there are three family functions associated with the protection of children, namely: the function of socialization, social placement functions/identities, and material protection function and emotional / affective. With these three functions, the family can make the fulfillment of needs / rights of children, among other things: survival, growth and development, protection, and participate optimally in accordance with human dignity.Keywords: Family function, child protection